Historical geographies of a colonised world: the renegotiation of New English colonialism in early modern urban Ireland, c. 1600-10 - McCarthy, Mark (Irish Geography, 2014)
Following the defeat of the Irish at the Battle of Kinsale (1601), the English Crown’s authority prevailed over most of Ireland and the loyalty of colonial outposts such as Cork no longer needed to be buttressed significantly. This paper examines the geopolitical environment of early seventeenth-century Ireland, by providing a case study of the renegotiation and strengthening of English colonial power from c. 1600-10 in an Irish urban space, namely the city of Cork. In examining the role of New English colonialism in forging the character of the early modem city of Cork from c. 1600-10, the wider military considerations related to New English imperial expansion at the time will be considered. A synthesis will also be provided of the resistance of the Cork citizens to the colonial strategies of the English Crown and Government in the early 1600s, as exemplified by the outbreak (and subsequent repression) of the ’Recusant Revolt’ in 1603, when the citizens of the city refused to proclaim James I as King of England. The stronger colonial presence that manifested itself in the aftermath of the suppressed ’Recusant Revolt’ is evident in a number of ways. Such strategies included the introduction by the colonial power of a policy of severe religious repression (predicated on a philosophy of English cultural supremacy) and a military strategy of locating garrisons at fortifications. These were accompanied by economic strategies that eroded Cork’s charter liberties in 1608 (whereby the Crown took back the duties of poundage, tonnage and petty customs which were collected in the port).